Child Prostitution: Phenomenon, Impact, Factors and Preventions - Fransiska Novita Eleanora; Reni Masrida; Sri Wahyuni; Indra Lorenly Nainggolan; Yapiter Marpi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The phenomenon of rampant acts of child prostitution causes children to lose their rights in relation to their protection, prostitution that makes children as victims is certainly an act that violates the law and decency, when children have to get education and study but instead get bad treatment and consequently hindered to live his life. In its development, prostitution which was originally a conventional crime became an unconventional crime where children can be victims or traded online through Facebook and Instagram in carrying out transactions or agreements through pimps or brokers. The impact of prostitution on children is that the child will be depressed, depressed and have a lot of daydreaming and not concentrating on learning while related to health can damage the reproduction of girls and cause infectious diseases such as AIDS/HIV. In addition, the factor of the occurrence of prostitution is due to economic factors where it is difficult to meet the necessities of life so that it justifies all means, and prevention can be done by increasing the family's understanding of the importance of child protection through an understanding of human rights, developing knowledge about the impact of prostitution on children and being consistent. to protect and supervise and guide children so as not to fall into the trap and also the need for the role and concern of the community to actively participate and be consistent and care about the government's efforts to provide guidance and supervision so that the practice of prostitution by minors does not occur again